2012
DOI: 10.1075/bct.43.07uso
|View full text |Cite
|
Sign up to set email alerts
|

Choice of strategies in realizations of epistemic possibility in English and Lithuanian

Abstract: The paper deals with the qualitative and quantitative parameters of equivalence between the realizations of epistemic possibility in English and Lithuanian. The focus of the contrast is on the auxiliary and adverb strategies (van der Auwera et al. 2005) in English (can, could, may, might vs. maybe, perhaps, possibly) as opposed to the corresponding modal verb and adverb/particle strategies in Lithuanian (galėti “can/could/may/might” vs. gal, galgi, galbūt, rasi, lyg ir “maybe/perhaps/possibly”). The purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…The comparatively rare epistemic use of gali ('can/may'.3prs) in Lithuanian humanities could be attributed to the general pattern of behaviour that Lithuanian modal verbs employ; there is a tendency for epistemic modality in Lithuanian to be expressed by means other than modal verbs (Usonienė & Šolienė 2010;Holvoet & Judžentis 2004). This claim is also confirmed by the studies that use parallel corpora.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparatively rare epistemic use of gali ('can/may'.3prs) in Lithuanian humanities could be attributed to the general pattern of behaviour that Lithuanian modal verbs employ; there is a tendency for epistemic modality in Lithuanian to be expressed by means other than modal verbs (Usonienė & Šolienė 2010;Holvoet & Judžentis 2004). This claim is also confirmed by the studies that use parallel corpora.…”
Section: Resultsmentioning
confidence: 99%
“…It will also investigate whether there are any differences in the use of this modal verb across different science fields. While there are undoubtedly extensive studies on the modality system in Lithuanian including the semantic profile of galėti ʻcan/could/may/mightʼ (see, for example, Holvoet 2007Holvoet , 2009Usonienė & Šolienė 2010;Šolienė 2013), they are primarily based on general Lithuanian or on corpora of fiction texts and do not focus on specialized discourses, such as academic discourse. There are some studies on hedging in Lithuanian academic discourse (Šinkūnienė 2008, 2011) but they only address the epistemic realizations of galėti ʻcan/could/may/mightʼ in small scale selfcompiled corpora of research articles.…”
Section: Introductionmentioning
confidence: 99%
“…Ar tikrai daroma prielaida ir įžvalgos yra pagrįstos ir teisingos tarpkalbinėje prancūzų-lietuvių kalbų erdvėje, bus galima spręsti atlikus išsamią tekstynu paremta devoir 'privalėti' ir jo vertimo atitikmenų kiekybinių ir kokybinių parametrų analizę. Reikėtų atkreipti dėmesį, kad kaip rodo jau atlikti kontrastyviniai anglų-lietuvių kalbų tyrimai (Usonienė, Šolienė 2010;Šolienė 2012), lietuvių kalboje episteminiam modalumui žymėti dažniausiai pasirenkama būtent adverbialinė raiška.…”
Section: Apibendrinamosios Pastabosunclassified
“…The reason behind this may be the fact that modal adverbials can only express epistemic meanings, which are most common in the use of must. Besides, as a number of studies have shown (Usonienė & Šolienė 2010;Šolienė 2012, 2013, Lithuanian opts for an adverbial strategy for the realization of epistemic modality. The semi-modals in question are usually translated by the Lithuanian modal verbs reikėti 'need' and turėti 'must/have to' which mostly encode deontic modality.…”
Section: Concluding Observationsmentioning
confidence: 99%
“…Still, the difference in the percentage indicates that must is more often translated into Lithuanian using an adverbial strategy rather than the verbal one (cf. van der Auwera et al 2005;Usonienė & Šolienė 2010;Šolienė 2012, 2013. Other TCs include the adverbials veikiausiai 'most probably', greičiausiai 'most likely' and galbūt 'maybe', as well as the verbs galėti 'can/ may' and tekti 'be gotten'.…”
Section: Lithuanian Correspondences Of Must Have To and Have Got Tomentioning
confidence: 99%